Kajian Unsur-unsur Semantik pada Cerpen Sepotong Senja untuk Pacarku Karya Seno Gumira Ajidarma 2023 - Mangunsong, Tio Artha Mega; Diliana, Ekfindar (Lembaga Yasin AlSys, 2023)
As a literary form, short stories contain a plethora of semantic components that are essential to communicating ideas to readers. It's crucial to comprehend the semantic components of short stories if you want to fully appreciate and analyze literary masterpieces. Because of this, the two main objectives of this study are to (1) examine the use of meaning kinds and (2) analyze the use of meaning relations in short stories. A descriptive approach is used in the research method, which is qualitative research. The primary data came from short tale texts, while the secondary data came from books, earlier research, journals, and other pertinent sources. The study's findings demonstrate how referential and non-referential semantic elements are used in the short story. Additionally, it was discovered that synonyms, antonyms, hypernyms, and hyponyms were used. Understanding the semantic components of this short story helps one better appreciate the point the author is trying to make. This study can advance literary studies and deepen our grasp of the semantic components of contemporary short stories.